2016
DOI: 10.1155/2016/3658527
|View full text |Cite
|
Sign up to set email alerts
|

The Regional Centralization of Electronic Fetal Heart Rate Monitoring and Its Impact on Neonatal Acidemia and the Cesarean Birth Rate

Abstract: Objective. The improvement of the accuracy of fetal heart rate (FHR) pattern interpretation to improve perinatal outcomes remains an elusive challenge. We examined the impact of an FHR centralization system on the incidence of neonatal acidemia and cesarean births. Methods. We performed a regional, population-based, before-and-after study of 9,139 deliveries over a 3-year period. The chi-squared test was used for the statistical analysis. Results. The before-and-after study showed no difference in the rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Original publications described the association between EFM patterns and fetal pH, 6,2729 but not the ability of EFM to predict and prevent injury. A recent meta-analysis summarized the findings from 13 randomized controlled trials, comparing the ability of EFM to identify infants with acidemia and morbidity to intermittent auscultation or intermittent EFM.…”
Section: Commentmentioning
confidence: 99%
“…Original publications described the association between EFM patterns and fetal pH, 6,2729 but not the ability of EFM to predict and prevent injury. A recent meta-analysis summarized the findings from 13 randomized controlled trials, comparing the ability of EFM to identify infants with acidemia and morbidity to intermittent auscultation or intermittent EFM.…”
Section: Commentmentioning
confidence: 99%
“…The improvement in the accuracy of FHR pattern interpretation through a continuous FHR centralization system is envisaged to be beneficial in reducing the incidence of neonatal acidemia ( Michikata et al, 2016 ). To improve the predictive efficacy of cardiotocography FHR, diagnostic algorithms are currently being investigated to be used in real-time computerized systems for decision support ( van Scheepen et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is consensus that the expert and algorithm-assisted FHR interpretation has the potential to improve standard clinical performance by facilitating the early recognition of tracing that is associated with metabolic acidemia [ 66 ]. Recently, a large population-based study showed that centralization of FHR monitoring with the help of specialists to interpret the results and determine clinical actions achieved an effective decrease in the rate of fetal acidemia without an increase in the rate of C-section births [ 67 ]. This implies that our institutional experience in predicting acidemia through FECG-derived parameters can be incorporated into training the attending obstetricians to help them take action early enough to decrease the incidence of neonatal acidemia and intrapartum death.…”
Section: Discussionmentioning
confidence: 99%